Design Thinking-Based Learning Assessment Guidelines to Improve Creative Thinking Skills - Widyastuti, Ni Luh Made Yulia; Jayanta, I Nyoman Laba (International Journal of Elementary Education, 2024)
The creative thinking process is a process that students go through to generate ideas or notions (creativity) in solving problems. Lack of attention to learning assessment in elementary schools that is appropriate and supports student creativity causes low creative thinking skills of students. This study aims to develop a design thinking-based learning assessment guidelines for grade V elementary school students in IPAS subjects and analyze the validity, practicality and effectiveness of the design thinking-based learning assessment guidelines. This research is development research with ADDIE model. The subjects in this study included learning assessment experts, teacher practitioners, and fifth grade students. This study used data collection techniques, namely questionnaires/surveys and tests. Data analysis techniques used qualitative, quantitative and inferential statistical analysis (t-test). The results of this study are the results of validation by learning assessment experts obtained very good qualifications, the results of practicality testing by teachers obtained very good qualifications, and the results of the effectiveness test of the design thinking-based learning assessment guidelines showed a significant difference in the creative thinking ability of grade V students in IPAS subjects before and after participating in learning by using a design thinking-based learning assessment guidelines. This indicates that the design thinking-based learning assessment guidelines are effective because these learning assessment guidelines can assist teachers in designing and implementing assessments to explore and improve students' creative thinking skills comprehensively.